Suboptimal management of hypertriglyceridemia in the outpatient setting is associated with the recurrent pancreatitis: A retrospective cohort study. Issue 43 (23rd October 2020) - Yan, Ping; Zhao, Hong-Xian; Chen, Xia
Abstract : Abstract: Hyperlipemia is a well-established etiology of acute pancreatitis. However, few data are available in the medical literature about the management of triglyceride levels in the outpatient setting in patients with hypertriglyceridemic acute pancreatitis (HTG-AP). We evaluated the blood triglyceride levels and followed the triglyceride management of patients with HTG-AP. This retrospective study enrolled patients with HTG-AP from January 2013 to March 2019 in the Affiliated Hospital of Southwest Medical of University. By reviewing the hospitalization records and the follow-up data, the clinical features, blood triglyceride levels, use of lipid-lowering medications and rate of blood triglyceride levels monitoring after hospital discharge were analyzed. A total of 133 patients (46 women, 87 men; median age at presentation 37.4 years) diagnosed with HTG-AP were enrolled in the study. Thirty-two patients (24.1%) presented with recurrent acute pancreatitis (RAP). Patients who had RAP were younger and had higher blood triglyceride levels than those with a single attack ( P  < .05). No difference in serum amylase levels, hospitalization duration or mortality rate were observed between non-recurrent acute pancreatitis and RAP patients. Lipid monitoring was only observed in 12.8% of patients and 10 patients (7.5%) took medications to control their blood triglyceride levels after hospital discharge. The follow-up of triglyceride levels in the outpatient setting were higher in RAP patients than in patients with non-recurrent acute pancreatitis ( P  < .05). Among the patients who measured their triglyceride levels after discharge, 83.3% of patients with RAP had at least 1 follow-up triglyceride level that was higher than 500 mg/dL, while no patients had an HTG-AP attack with a triglyceride level higher than 500 mg/dL. Triglyceride levels after hospital discharge higher than 500 mg/dL may be associated with an increased risk of relapse of clinical acute pancreatitis events. Inappropriate management for triglyceride control in the outpatient setting may be associated with an increased risk of relapse of clinical HTG-AP events.